THE MONETARY SYSTEM OF UKRAINE: PROBLEMS OF FORMATION AND PROSPECTS FOR DEVELOPMENT - Гвоздей, Наталія (SWorldJournal, 2026)
This article examines the problems of establishing and developing Ukraine's monetary system in the context of transformation processes and contemporary global challenges. The author emphasize that Ukraine's monetary system was formed alongside the develop